PENJADWALAN PREVENTIVE MAINTENANCE MESIN MILL DENGAN MENGGUNAKAN METODE OEE, SIX BIG LOSSESS DAN FMECA - Larsen, Herwin; Salomon, Lithrone Laricha; Saryatmo, M Agung (Jurnal Mitra Teknik Industri, 2024)
In the production process, the machine is an important factor in the ongoing production process. In maintaining the continuity of engine performance, it is necessary to have good engine maintenance and regular scheduling. However, some companies often ignore this and machine breakdowns occur and result in prolonged downtime. From the observation results it was found that the mill machine has the time with the greatest downtime. The research was conducted using the OEE method to measure the level of productivity and effectiveness of the machine. After processing the data, the OEE value was 54.79%. Followed by data processing using Six Big Lossess. Obtained from the calculation of the Six Big Lossess that there are 2 losses that have the greatest value, namely idle and minor stoppage losses of 85.7% and reduced speed losses of 57.6%. Followed by fishbone analysis. After being analyzed using a fishbone diagram, it was found that the causal factors of the losses were found. The analysis was continued using FMECA and 3 failure modes were obtained with the highest RPN values, namely unscheduled machine maintenance, raw materials from the previous station were not on time, and there was no guide for good machine use. In overcoming the problem, MTBF scheduling is made for each engine component. For the servo pipe component, a re-examination was carried out on August 26, 2022, hydraulic axles on November 21, 2022, timing belt components on June 3, 2023, hydraulic hose components on May 23, 2023, wielding insulator components on April 8, 2023. This can optimize preventive maintenance so that machine efficiency can increase.